PENGARUH HARD SKILL DAN SOFT SKILL TERHADAP KINERJA PEGAWAI PADA KANTOR DIANS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN PINRANG - Jaya, Hendri Adi; Rosadi, Imran (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of hard skills and soft skills on employee performance at the office of Dinas Pendidikan Dan Kebudayaan Kabupaten Pinrang. The data collection techniques used in this study were observation and questionnaires. The sample in this study amounted to 51. The data analysis technique in this study used multiple linear regression analysis with the help of a computerized system (computer program IBM Statistics SPSS 26). The results of the study indicate that partially Hard Skill (X1) has a positive and significant effect on Employee Performance (Y). Partially Soft Skill (X2) has a positive influence on Employee Performance (Y).